Cyprus : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2004 Article IV Consultation highlights that economic growth in Cyprus has begun to rebound following a more modest performance in 2002-03, recovering in real terms to about 3 1\2 percent in 2004, mainly driven by an increase in domestic demand. Real per capita income has continued to rise, now reaching above 80 percent of the average European Union 25 income level when adjusted for purchasing power. Looking ahead, growth is estimated at close to 4 percent in 2005, reflecting an improved external environment.